The influence of TikTok daily reward gamification and social presence on impulsive buying behavior: The mediating role of emotional arousal on social commerce platforms - Hatta, Agam Rahman; Miesvontoko, Aby; Hidayat, Desman (Edelweiss Applied Science and Technology, 2025)
This study explores the influence of TikTok’s Daily Reward gamification, user experience, and social presence on impulsive buying behavior within social commerce, with emotional arousal as a mediating variable. The research addresses the growing prevalence of impulsive consumer behavior driven by interactive and emotionally engaging platform features such as gamification and live streaming. Using a quantitative approach, data were collected from 127 TikTok Shop users through an online survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that both Daily Reward gamification and social presence significantly affect emotional arousal, which in turn moderately influences impulsive buying behavior. However, emotional arousal was only found to significantly mediate the relationship between gamification and impulsive buying behavior, while its mediating role between social presence and impulsive buying was not statistically supported. These findings underscore the importance of emotionally engaging platform features in stimulating unplanned consumer purchases and provide strategic insights for businesses aiming to enhance user interaction and conversion rates on social commerce platforms.